Cognitive and behavioural processes in adolescents with social anxiety disorder - Leigh, E; Percy, R; Clark, D; Creswell, C; Waite, P (Elsevier, 2023)
Background: A better understanding of the processes that maintain social anxiety disorder (SAD) in adolescents could improve treatment outcomes. This study aimed to establish whether cognitive and behavioural processes known to be important in the maintenance of adult SAD are observed in adolescent populations and whether they are specific to SAD. Methods: We recruited three groups of adolescents (12-18y): (1) 90 adolescents with a SAD diagnosis, (2) 58 adolescents with an anxiety disorder that was not SAD, and (3) 45 community-based adolescents. Participants completed measures of negative social cognitions, social attitudes, safety behaviours, self-focused attention, and social anxiety, anxiety, and depression symptoms. Results: The clinical SAD sample endorsed higher levels of negative social cognitions, attitudes, and safety behaviours compared to both control groups. Self-focused attention was higher in the clinical SAD sample compared to the anxiety clinical control group but not compared to the community control group. Conclusions: This study provided evidence of SAD-specific mechanisms including negative social cognitions, attitudes and safety behaviours in adolescents. The study did not provide evidence of disorder-specific mechanisms of self-focused attention but this may have been due to methodological limitations. These findings indicate avenues for further research and point to the potential value of Cognitive Therapy for the treatment of adolescent SAD.